Contemporary Art and the Problem of Music: Towards a Musical Contemporary Art. Issue 2 (June 2021) - BARRETT, G. DOUGLAS
Abstract: This article elaborates the art-theoretical concept of 'the contemporary' along with formal differences between contemporary music and contemporary art. Contemporary art emerges from the radical transformations of the historical avant-garde and neo-avant-garde that have led to post-conceptual art – a generic art beyond specific mediums that prioritizes discursive meaning and social process – while contemporary music struggles with its status as a non-conceptual art form that inherits its concept from aesthetic modernism and absolute music. The article also considers the category of sound art and discusses some of the ways it, too, is at odds with contemporary art's generic and post-conceptual condition. I argue that, despite their respective claims to contemporaneity, neither sound art nor contemporary music is contemporary in the historical sense of the term articulated in art theory. As an alternative to these categories, I propose 'musical contemporary art' to describe practices that depart in consequential ways from new/contemporary music and sound art.